Autonomous vehicle platoon modeling and control using PID and linear quadratic regulator - Gunagwera, Alex (İstanbul Sabahattin Zaim Üniversitesi, 2022)
With over 50 million cars being produced annually since 2010, the number of vehicles on the roads increases throughout the world. With the increase in vehicle population comes challenges and problems in efficient and safe transportation via roads. Major problems include road accidents, global warming due to emissions, efficient energy utilization and road usage to mention but afew. The autonomous vehicle platooning concept provides both a promising solution and an enhancement approach to intelligent transport systems. Among the benefits this promising concept presents are reduced fuel consumption and, hence emissions, efficient road usage among others. The autonomous vehicle platooning industry, however, still faces a great deal of issues and challenges ranging from string stability, safety guaranties, efficient communication to accurate control. In this study, autonomous vehicle platooning modeling and control using PID and LQR are presented. The algorithms are verified using two scenarios on 3D vehicles simulated used Gazebo and ROS. In the first scenario the platoon leading vehicle mainly accelerated, travelled with constant speed, and decelerated to rest. In the second scenario, however, the leading vehicle travelled with uncertain and constantly varying velocities. Results from both scenarios are then presented and summarized in graph and tabular forms. In both scenarios, platoon stability, especially after the initial transient response was achieved, the following effect for the platoon members in the performed simulations is also guaranteed and a steady state error of 0m was obtained by both control strategies.

2010 yılından bu yana yılda 50 milyonun üzerinde otomobil üretiliyor ve dünya genelinde yollardaki araç sayısı artıyor. Araç popülasyonundaki artışla birlikte karayolu ile verimli ve güvenli ulaşımda zorluklar ve sorunlar ortaya çıkmaktadır. Başlıca sorunlar arasında trafik kazaları, emisyonlardan kaynaklanan küresel ısınma, verimli enerji kullanımı ve yol kullanımı sayılabilir. Otonom araç müfreze konsepti, akıllı ulaşım sistemlerine hem umut verici bir çözüm hem de iyileştirme yaklaşımı sağlar. Bu umut verici konseptin sunduğu faydalar arasında daha az yakıt tüketimi ve dolayısıyla emisyonlar ve diğerlerinin yanı sıra verimli yol kullanımı yer alıyor. Bununla birlikte, otonom araç müfreze endüstrisi, dizilim kararlılığı, güvenlik garantileri, verimli iletişimden doğru kontrole kadar birçok sorun ve zorlukla karşı karşıyadır. Bu çalışmada, PID ve LQR kullanılarak otonom araç müfreze modellemesi ve kontrolü sunuldu. Algoritmalar, iki senaryo kullanılarak Gazebo ve ROS 3B ortamlarında simüle edilerek doğrulandı. İlk senaryoda, müfrezeye liderlik eden araç hızlandı, sabit hızla gitti ve durmak için yavaşladı. İkinci senaryoda, lider araç belirsiz ve sürekli değişen hızlarla yol aldı. Her iki senaryodan elde edilen sonuçlar daha sonra grafik ve tablo formlarında sunuldu ve özetlendi. Her iki senaryoda da, ilk geçici tepki elde edildikten sonra müfreze kararlılığı elde edildi ve takip de garanti edildi. Her iki kontrol stratejisi ile de 0m'lik bir kalıcı hal hatası elde edildi.
Linear quadratic regulator ve PID controller ile otonom araç müfrezesinin modellenmesi ve kontrolü
Keywords: Autonomous vehicles; Autonomous vehicle platoons; Control theory; Intelligent transport systems; LQR; PID; Akıllı ulaşım sistemleri; Kontrol teorisi; LQR otonom araçlar; Otonom araç takımları